Treatment of choledochal lithiasis by laparoscopy, a case series of the Surgical Clinic 2 of the Maciel Hospital - Moreira, Emilia; Pontillo, Mauricio; Hernández, Rodrigo; Rodríguez Temesio, Gustavo (Cirugía del Uruguay, 2020)
Background: Biliary lithiasis is a high prevalence disease among general population being one of the most common surgical cause to attend to ambulatory appointment or to the emergency room. Due to the disease high prevalence and the potential complications, treatment is indicated. The best treatment option is still a matter of debate, admitting either surgical, endoscopic or percutaneous treatment. The aim of this series was to present the surgical management of choledocholithiasis, either as symptomatic presentations or as an incidental finding during intraoperative colangiography, at Surgical Clinic 2, Maciel Hospital. Methods: An electronic search was done among all colecistectomie's records between January 1st and October 7th, 2018, selecting those with choledocholithiasis confirmed by intraoperative cholangiography. Results: 115 colecystectomy were done in the time period previously mentioned, 113 patients had laparoscopic colecistectomies and 2 patients had open conversions, choledocholitiasis was confirmed in 20 cases. Stone clearance was done with Dormia basket, angioplasty balloon catheter, Randall stone forceps and flushing with saline, it was successful in 18 cases. Discussion: Either transcistic or choledochotomy approach allowed to solve the disease in one surgical act. Intraoperative cholangiography was successful in 80% of cases and lithiasis extraction was complete in 90% of cases, no difference with previous published works found. Conclusions: Transcystic or choledochotomy approach is a safe and effective treatment